Does monetary policy solely correct disequilibrium in the balance of payment? Evidence from the developing world - Muhammad Azam Khan (Journal of Central Banking Theory and Practice, 2023)
Monetary policy and balance of payments (BoP) are the key parameters in any country's economy performance. This study is an attempt to re-explore the impact of domestic credit provided by the financial sector, real interest rate, real GDP growth, inflation rate, and exchange rate on the balance of payments by net foreign assets (NFA) in 17 developing countries over 1982-2019. The most appropriate empirical strategy has been implemented to obtain robust empirical results. The results indicate that domestic credit, interest rate, inflation and exchange rate have a significantly negative, while real GDP growth has a significantly positive impact on NFA. The results of Granger causality test reveals a bidirectional causality between domestic credit and NFA, between exchange rate and NFA. Furthermore, in the case of individual country analysis, overall empirical estimates of three estimators are acceptable for 17 individual countries although some dissimilarities are found between the countries in the magnitude of estimated coefficients of variables and level of significance . Empirical findings suggest that to correct the disequilibrium in BoP, central banks (monetary authorities) need to give equal consideration to other policy measures along with the monetary instruments to accomplish stability in a country's BoP account.
Keywords: E4; E5; E31; O4; 330; Domestic credit; inflation; income; balance of payments; monetary policy; developing economies